Triploid cultivars of Cymbidium act as a bridge in the formation of polyploid plants - Man-Man Li; Qing-Lian Su; Jun-Rui Zu; Li Xie; Qian Wei; He-Rong Guo; Jianjun Chen; Rui-Zhen Zeng; Zhi-Sheng Zhang (Frontiers in Plant Science, 2022)
Triploid is considered a reproductive barrier and also a bridge in the formation of polyploids. However, few reports are available in Cymbidium. In this study, diploid ‘Xiaofeng’, sexual triploid ‘Yuchan’ and ‘Huanghe’ of Cymbidium were used to evaluate hybridization compatibility of the triploids. Results showed that the sexual triploids were fertile whether they were used as male or female parents. ‘Yuchan’ produced male gametes of 1x, 1x~2x, 2x, 2x~3x, and 3x at frequencies of 8.89%, 77.78%, 6.67%, 3.33%, and 3.33%, respectively; while ‘Huanghe’ produced 3.33% 1x, 80.00% 1x~2x, 8.89% 2x, 5.56% 2x~3x, and 2.22% 3x male gametes. The cross of ‘Xiaofeng’ with ‘Yuchan’ produced progenies with a wide range of ploidy levels, including one diploid, 34 2×~3× aneuploids, 12 triploids, and one tetraploid, indicating that male gametes produced by sexual triploid were fertile and could be transmitted and fused with egg cells. On the other hand, 10 progenies obtained from the cross of ‘Yuchan’ × ‘Xiaofeng’ were all aneuploids. The cross of ‘Yuchan’ with ‘Huanghe’ produced 40 progenies including three 2×~3× aneuploids, nine 3×~4× aneuploids, 21 tetraploids, six 4×~5× aneuploids, and one pentaploid, suggesting that 2x gametes, instead of the unreduced ones played a more important role in the formation of tetraploids. The survival rates of the hybrids were all above 80.00%, with the tetraploids at 96.67%. Cytological analysis revealed that during meiosis of sexual polyploids, two chromosome sets of the 2n gamete were inclined to enter into the same daughter cell, resulting in the production of 2x gametes. Our results indicate that the triploid cymbidiums are not reproductive barrier but serve as a bridge in the formation of polyploid plants.